Fusing subjective and objective factors:a dynamic approach to evaluating reputation for IoT search - Hui-bing ZHANG; Chao LI; Xiao-li HU; Ya ZHOU (Tongxin xuebao)
Compared with the traditional Internet search,IoT search data center needs a higher data quality.In order to effectively motivate data owners to continuously provide higher quality data,the center needs pay the corresponding rewards to them according to the quality of data (QoD).As a result,QoD and the trustworthy evaluation become a basic problem for the development of IoT search.To address this problem and support data selection of IoT center,a dynamic reputation model was proposed to comprehensively assess the reputation of data owners.In detail,first,an approach to assessing the subjective and objective quality was proposed and mechanism of interactive discount and reputation attenuation was designed.Then,fusing subjective and objective factors,a novel dynamic reputation evaluation scheme was presented.Last,in order to get constraint relation of interaction times,discount,payment price,and data cost,an economic analysis based on signaling game was conducted.Experiment results show that the proposed approach can reflect dynamic change of QoD effectively,and provide the basis for data selection.It also can be adapted to real-time and dynamic of IoT search.